PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LIKUIDITAS, GROSS PROFIT MARGIN DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL - Rosa Chantika Roosiana Dewi; Ida Nurhayati (Jurnal Akuntansi dan Pajak, 2023)
The purpose of the capital structure itself is to combine both permanent and current sources of funds in the company as an effort to avoid bankruptcy. Financial performance is an illustration of the company's success achievement which can be interpreted as the results that have been achieved for the various activities that have been carried out. The implementation of the capital structure must handled carefully and properly in order to avoid delays or setbacks in economic competition. In fact, the capital structure is one of the most fundamental things in the success of building a company, especially in corporate finance. This study aims to determine the effect of profitability, company size, liquidity, gross profit margin and sales growth on capital structure. The population in this study are LQ45 companies listed on the Indonesia Stock Exchange (IDX). The results of the research that has been done show that the profitability and company growth variables have a negative and insignificant effect on capital structure, company size and gross profit margin variables have a positive and insignificant effect on capital structure and liquidity variables have a negative and insignificant effect on capital structure.